Reforming Legal Decision-Making: A Study of Hindsight Bias on Judicial Impartiality - Zahra, Salma; Azizan, Akmal; Sophia, Sally; Perai, Nurajam (Jurnal Hukum dan Peradilan, 2024)
Legal decision-making is heavily influenced by cognitive processes like memory and judgment, which are vulnerable to biases such as false autobiographical memories, hindsight bias, and pretrial publicity. These flaws can lead to wrongful convictions, biased negligence assessments, and compromised impartiality, undermining legal fairness. This study examines these cognitive vulnerabilities, analyzing their mechanisms and proposing strategies to reduce their impact. A literature review of empirical research from 2018 to 2023 integrates findings from psychology, neuroscience, and law. The study highlights how these biases affect legal outcomes and suggests practical solutions like simplified judge instructions, structured interrogation protocols, and bias awareness training. The research uses Cognitive Load Theory, aiming to enhance the integrity of legal processes and provide evidence-based recommendations to improve the fairness and accuracy of legal decisions.